Applying lEAN Management Methods and Role to Achieving Administrative and Financial Performance in Business Organizations (Field Study) - Ismael, Dar Elneim Abakr Mohamed; Ahmed, Hoda Diab (Journal of Economic, Administrative and Legal Sciences, 2025)
The research aimed to study the application of lean management methods and their role in the efficiency of administrative and financial performance in business organizations, and the variables of the study were lean management methods as an independent variable and administrative and financial performance efficiency as a dependent variable, and to achieve the objectives of the study, a random sample was selected from the study community. The study relied on the questionnaire as the main tool for data collection. The questionnaire was distributed electronically to the study sample of 60 individuals, after conducting an exploratory study on a pilot sample of 20 individuals in order to conduct the necessary tests to verify the stability and reliability of the study tool. To analyze the collected data, the researchers used some statistical tests and methods through statistical programs specialized in data analysis such as SPSS. Based on the results of the statistical tests, the study concluded a number of results, the most important of which are:1- The existence of a statistically significant effect between the independent variable and the dependent variables.2- The application of agile management methods in the administrative side of business organizations helps to develop the organizational structure of business organizations, and enhances the ability of administrative teams to make quick decisions, which leads to an increase in the efficiency of administrative and financial performance.3- The application of agile management methods reduces operational costs and financial waste.Among the most important recommendations: The need to apply agile management methods in business organizations of all types to create flexibility and achieve efficiency in administrative and financial performance.
Keywords: LEAN management; administrative performance; financial performance; efficiency business organizations